Impact of early disease progression and surgical complications on adjuvant chemotherapy completion rates and survival in patients undergoing the surgery first approach for resectable pancreatic ductal adenocarcinoma – A population-based cohort study. (3rd March 2016) - Labori, Knut J.; Katz, Matthew H.; Tzeng, Ching W.; Bjørnbeth, Bjørn A.; Cvancarova, Milada; Edwin, Bjørn; Kure, Elin H.; Eide, Tor J.; Dueland, Svein; Buanes, Trond; Gladhaug, Ivar P.
Abstract : Background. Multimodality treatment (MMT) improves survival for patients with pancreatic ductal adenocarcinoma (PDAC). The surgery-first (SF) strategy is the most universally accepted approach. Material and methods. Population-based retrospective cohort study of all cases of resectable PDAC from 2006 to 2012. Patients were planned for adjuvant chemotherapy (AC) with the Nordic 5-fluorouracil/leucovorin regimen. Reasons for and rates of failure to complete AC, postoperative major complications (PMC), and overall survival (OS) were analysed. Results. Of 203 patients, 85 (41.9%) completed AC, 41 (20.2%) failed to complete AC, and 77 (37.9%) never initiated AC. Primary reasons for not initiating or completing AC were early disease progression (34.7%), postoperative complications/poor performance status (32.2%), and age > 75 years (24.6%). Median OS in the whole cohort was 17.0 months, and 20.0 months in patients who initiated AC. Median OS in patients who completed AC was higher than in patients who did not (25.0 months vs. 12.0 months, p < 0.001). PMC (n = 41) were associated with decreased initiation rate (p < 0.001) and completion rate (p = 0.007) of AC, and decreased median OS (11.0 months vs. 19.0 months, p = 0.028). Among patients with R1 resection, PMC again were associated with worse median OS (8.0 months vs. 16.0 months, p = 0.028). Multivariate analysis demonstrated that completion of MMT and tumour grade (G1/G2) were related to mortality rate (p < 0.001). Mortality risk for patients who completed AC was reduced also when adjusting for competing risk (SHR 0.426, p < 0.001). Conclusions. MMT completion is strongly associated with reduced mortality risk in patients with resectable PDAC undergoing the SF approach. Early disease progression and PMC/poor performance status preclude MMT completion in more than one third of the patients. These reasons for failure to complete MMT underscore the need for strategies to improve patient selection and reduce surgical morbidity in patients with resectable PDAC.